The BRCA1 Tumor Suppressor Binds to Inositol 1,4,5-Trisphosphate Receptors to Stimulate Apoptotic Calcium Release - Hedgepeth, Serena C. (J Biol Chem, 2015)
The inositol 1,4,5-trisphosphate receptor (IP(3)R) is a ubiquitously expressed endoplasmic reticulum (ER)-resident calcium channel. Calcium release mediated by IP(3)Rs influences many signaling pathways, including those regulating apoptosis. IP(3)R activity is regulated by protein-protein interactions, including binding to proto-oncogenes and tumor suppressors to regulate cell death. Here we show that the IP(3)R binds to the tumor suppressor BRCA1. BRCA1 binding directly sensitizes the IP(3)R to its ligand, IP(3). BRCA1 is recruited to the ER during apoptosis in an IP(3)R-dependent manner, and, in addition, a pool of BRCA1 protein is constitutively associated with the ER under non-apoptotic conditions. This is likely mediated by a novel lipid binding activity of the first BRCA1 C terminus domain of BRCA1. These findings provide a mechanistic explanation by which BRCA1 can act as a proapoptotic protein.